Cataract surgery in a patient with bilateral necrotising scleritis and peripheral ulcerative keratitis associated with granulomatosis with polyangiitis (Wegener’s granulomatosis) - Stanojlović, Svetlana; Glišić, Selimir; Arandjelović, Snežana; Kalezić, Tanja; Dačić Krnjaja, Bojana; Savić, Borivoje (Vojnosanitetski pregled, 2021)
Introduction. We report a rare case of cataract surgery in a patient with an extreme, widespread anterior staphyloma following severe bilateral necrotising anterior scleritis associated with granulomatosis with polyangiitis (GPA). Case report. A 61-year-old man with a history of GPA developed bilateral, rapidly progressive necrotising scleritis and peripheral ulcerative keratitis (PUK). Inflammation compromised the entire anterior globe and peripheral cornea in both eyes. More than 90% of the surface area healed within 8 weeks, following the treatment with 3 pulsed doses of methylprednisolone in addition to the cyclophosphamide treatment. Systemic steroid therapy was slowly tapered over a period of 6 months. Extraordinary scleral loss with a uveal bulge developed, following severe necrotising anterior scleritis associated with PUK. Once the full remission had been achieved after 6 months, uncomplicated phacoemulsification was performed in his left eye, the only functional one. Conclusion. Preoperative and postoperative control of inflammation, careful surgical planning, and meticulous surgical techniques are critically important for optimal surgical outcome in such patients. To our knowledge, phacoemulsification in a patient with coexisting uveitic cataract and severe anterior staphyloma has not been previously reported.